Mathematical Literacy Skills: A Survey in Secondary Schools - Arifta Nurjanah; Dimas Candra Saputra (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This study aims to present the abilities of junior high school students' mathematical literacy in Sleman Regency, Yogyakarta Special Region Province, Indonesia. This survey used proportional random sampling to sample 428 eighth graders from fourteen schools. A mathematical literacy task for this study has been tested for validity and reliability. The data were analyzed by converting the test scores using interval scales to categorize the abilities. Based on the analysis, the mathematical literacy skills of students were generally included in the low category, with a distribution of 62.15% of students in the very low category, 13.32% in the low category, 14.02% in the medium category, 5.37% in the high category, and 5.14% in the very high category. They were: 1) in a low category for the formula and employ processes, and a very low category for the interpreting process; 2) in a low category for the Quantity and Uncertainty Data content, and a very low category for the change and relationship and space and shape content; and 3) in a low category for the Personal and Occupational context, and a very low category for the social and Scientific context. The results of this study are expected to be a consideration for related parties to improve the quality of education, especially in learning mathematics.